Aerobic and anaerobic training: effects on cognitive function in adolescents - Krivolapchuk I.A. ,; Chernova M.B. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the impact of bioenergetic factors on the physical performance of young athletes during cognitive tasks of different difficulty levels. Methods and structure of the study. The research project included a group of young athletes aged 13 to 14, who participated in cycling and running competitions over medium and long distances. The study involved 97 participants. The cognitive load was simulated using a two-minute task with letter tables in two modes: «autotemp» and «maximum tempo». Results and conclusions. It has been shown that high aerobic, anaerobic glycolytic and anaerobic alactic capacity are associated with favorable changes in FS under conditions of intense cognitive load. The results of the study give reason to believe that the complex use of aerobic and anaerobic physical activity in the process of sports improvement creates the prerequisites for increasing stress resistance and optimizing the physical activity of the body of young athletes not only during muscular, but also intense cognitive activity.